1977
DOI: 10.1093/infdis/136.5.623
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Double-Blind Comparison of Reactogenicity, Immunogenicity, and Protective Efficacy of Whole-Virus and Split-Product Influenza Vaccines in Children

Abstract: A double-blind randomized study with bivalent influenza virus vaccines was conducted to compare the local and systemic reactions and immunogenicity of a whole-virus vaccine and a split-product vaccine in children. Fevers of greater than 100 F were more frequent after vaccination with whole-virus than split-product vaccine especially in children one to four years old (69% vs 22%; P less than 0.01). Fevers of greater than or equal to 103 F did not occur in children who previously had been given influenza virus v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 13 publications
3
62
0
Order By: Relevance
“…It has been reported that split-product influenza vaccine is adequately immunogenic while maintaining a lower incidence of adverse reactions than those to wholevirus vaccine (8,9). The adverse reactions reported in this study were also infrequent, and even when reported, were chiefly local ones, mild in nature and of short duration.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…It has been reported that split-product influenza vaccine is adequately immunogenic while maintaining a lower incidence of adverse reactions than those to wholevirus vaccine (8,9). The adverse reactions reported in this study were also infrequent, and even when reported, were chiefly local ones, mild in nature and of short duration.…”
Section: Discussionsupporting
confidence: 46%
“…The most important factor may have been the considerably high HAI antibody titers induced by natural infection, which persisted until the next vaccination season, and resulted in a poorer response to the same type (or subtype) of virus antigen as the causative one during the protracted influenza epidemic (5,9,20). Furthermore, quantitatively unfixed vaccine antigens might be cited as potential factors (8,10).…”
Section: Discussionmentioning
confidence: 99%
“…However, 30-70 % of participants in the various groups did experience some reaction. Gross et al (1977) observed that prior influenza immunization reduces reactions following subsequent immunization with related antigens. In our group A it is remarkable that pupils receiving an influenza vaccine for the first time indicate less reactions than those immunized previously in 1976.…”
Section: Resultsmentioning
confidence: 99%
“…(Mostow et al 1969;Nicholson et al 1979;Jennings, Potter & Massey, 1981;Potter, 1982). The original whole virus vaccines were relatively reactogenic, and have been widely replaced by aqueous subunit vaccines prepared from highly purified virus particles, and these vaccines are equally immunogenic in periods of antigenic drift (Rymer et al 1966;Gross et al 1977;Miles et al 1982). In contrast, improvements in vaccines and the accumulated knowledge of the responses to immunization have not provided completely satisfactory influenza vaccines, and a significant number of vaccinees remain susceptible to challenge by natural virus infection (Hobson, 1972;Potter, 1982).…”
Section: Introductionmentioning
confidence: 99%